Assessment of different internal flow blockage scenarios for LFR fuel assemblies with different configurations. (1st December 2022) - Luo, Xiao; Zhang, Kefan; Duan, Wenshun; Chen, Hongli
Highlights: The influence of internal flow blockage scenarios on fuel assembly thermal–hydraulic parameters is performed based on the subchannel method. Several blockage parameters are chosen as input parameters and the influence of different blockage parameters is analyzed. Two LFR fuel assemblies with different configurations are chosen to identify the differences and commonalities of their thermal–hydraulic characteristics under different flow blockage conditions. Abstract: Flow blockage accident is identified as one of the most serious accidents in LFR (lead-cooled fast reactor) due to the concealment of the accident process and the severity of the accident consequences. The main goal addressed in this paper is to assess the influence of different flow blockage scenarios on the thermal–hydraulic parameters of LFR single-wrapper fuel assemblies (FAs), and to identify the differences and commonalities of thermal–hydraulic response characteristics between two typical-design FAs under different flow blockage conditions. The subchannel method is adopted to implement a detailed assessment of different blockage parameters, including the axial/radial position, thickness, area and the thermal conductivity of the blockage. A case matrix is constructed based on the control variable method and covers various blockage conditions between two FAs with different configurations, which represent typical FA designs including both forced-circulation and natural-circulation LFRs. Current results show that different blockage parameters have different influences on the fluid behaviors (such as dynamic pressure drop and recirculation phenomena) and heat transfer characteristics (such as peak temperature of cladding, pellet and coolant and outlet temperature distribution). Meanwhile, different FAs show some similar phenomena and also differences in various flow blockage scenarios.